Preparation method of negatively charged polytetrafluoroethylene membrane, negatively charged polytetrafluoroethylene membrane and application of negatively charged polytetrafluoroethylene membrane

By combining bifunctional aminosiloxane coupling agents and ARGET ATRP technology on PTFE membranes, the internal pore structure of PTFE membranes was made hydrophilic and the surface was charged, which solved the fouling problem caused by the hydrophobicity of PTFE membranes in water systems and improved the hydrophilicity and antifouling ability of the membranes.

CN121244024AActive Publication Date: 2026-01-02TIANJIN SEA WATER DESALINATION & COMPLEX UTILIZATION INST STATE OCEANOGRAPHI +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511803517.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-03
Publication Date
2026-01-02
Estimated Expiration
2045-12-03

AI Technical Summary

Technical Problem

Existing PTFE membranes suffer from organic pollution problems due to their hydrophobicity in aqueous systems. Furthermore, existing modification methods are difficult to achieve hydrophilicity of the internal pore structure and large-scale production. Chemical oxidation and high-energy beam treatment present safety and equipment complexity issues.

Method used

A bifunctional aminosiloxane coupling agent is used for preliminary and deep dehydration condensation. Combined with ARGET ATRP technology, negatively charged hydrophilic monomers are grafted onto the PTFE membrane surface to form a stable modified layer with high cross-linking degree, thereby achieving simultaneous hydrophilization and charge modification of the membrane pores inside and outside.

Benefits of technology

The prepared negatively charged polytetrafluoroethylene membrane has excellent hydrophilicity and durability, and can effectively utilize electrostatic repulsion effect to alleviate membrane fouling, improve service life and filtration efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121244024A_ABST
    Figure CN121244024A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a negatively charged polytetrafluoroethylene membrane, the negatively charged polytetrafluoroethylene membrane and application of the negatively charged polytetrafluoroethylene membrane, and relates to the technical field of membrane materials. The preparation method of the negatively charged polytetrafluoroethylene membrane comprises the following steps: putting a polytetrafluoroethylene membrane into an alcohol solution containing a siloxane coupling agent, and carrying out first soaking treatment; placing the treated polytetrafluoroethylene film in an acidic aqueous solution, and carrying out secondary soaking treatment to complete hydrolysis primary dehydration condensation; carrying out drying treatment on the treated polytetrafluoroethylene film to finish deep dehydration condensation; the preparation method comprises the following steps: bonding an atom transfer radical polymerization initiation site on the surface of a polytetrafluoroethylene membrane, activating a regenerated catalyst through electron transfer, carrying out atom transfer radical polymerization reaction, and grafting a negatively charged hydrophilic monomer on the surface of the polytetrafluoroethylene membrane with the initiation site to obtain the negatively charged polytetrafluoroethylene membrane. The negatively charged polytetrafluoroethylene membrane disclosed by the invention has excellent hydrophilicity and charge long-term effect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of membrane materials for water treatment, in particular to a preparation method of a negatively charged polytetrafluoroethylene membrane, the negatively charged polytetrafluoroethylene membrane and application thereof, and especially to a hydrophilic and durable negatively charged polytetrafluoroethylene membrane, a preparation method and application thereof. BACKGROUND

[0002] Polytetrafluoroethylene (PTFE) membrane is a microporous material produced by special stretching process of PTFE resin. The inherent hydrophobicity of PTFE is the basis for its excellent waterproof and antifouling performance, but this property also limits its application in water system. Although PTFE membrane has the characteristics of low surface energy, due to its inherent strong hydrophobicity, it still encounters the problem of organic pollution. Therefore, it is still a challenge to build a firm hydrophilic coating on the surface of PTFE. After hydrophilic modification, the water flux of PTFE membrane increases significantly, the operating energy consumption decreases, and the anti-fouling ability of the membrane is enhanced, so that the application of PTFE membrane in water environment becomes possible.

[0003] Generally, the hydrophilic modification methods of PTFE membrane include etching modification, grafting modification and physical modification. Etching modification destroys the C–F or C–C bond on the surface of PTFE by chemical oxidation or high-energy beam treatment. This process introduces polar functional groups (such as amino, carboxyl and hydroxyl) into the PTFE molecular chain, thereby realizing hydrophilic modification. Etching modification is usually used as the basis for grafting modification to provide anchoring sites for subsequent introduction of hydrophilic components. However, chemical oxidation usually degrades the nodule-fiber structure of PTFE, which has an adverse effect on the macroscopic morphology and mechanical properties of the membrane. In addition, due to the dependence on dangerous chemicals and the generation of difficult-to-recycle waste liquid, chemical oxidation faces difficulties in large-scale implementation. Although high-energy beam treatment has advantages in safety and reliability, it can effectively introduce polar functional groups on the surface of PTFE membrane, but it faces the challenges of expensive and complex equipment, difficulty in continuous large-scale production or batch treatment. More importantly, this method usually only modifies the surface and is difficult to realize the hydrophilization of the internal pore structure. Therefore, only enhancing the surface hydrophilicity has limited effect on reducing the permeation resistance of the membrane.

[0004] In-situ polymerization is also an effective method to improve the water wettability and permeability of PTFE membrane. Although polymerization occurs during the modification process, the modified layer does not form a chemical bond with the PTFE bulk structure. Therefore, in-situ polymerization is still classified as a form of physical modification, and is widely used in large-scale production due to its simple operation and mild reaction conditions. Although the small molecule modifier used in in-situ polymerization can easily penetrate the membrane pores, its relatively low polymerization efficiency still limits the effective coating of the hydrophilic network on the PTFE fibers. Although in-situ polymerization is a mild and environmentally friendly technology, it is simpler and easier to operate than surface grafting modification, but it still has some limitations. These limitations include insufficient hydrophilicity of the membrane due to incomplete coverage of the hydrophilic polymer, and pore blockage due to inaccurate control of the modification process.

[0005] The suspended particles and colloidal substances in the mine water are usually negatively charged, which is an important reason why organic membranes easily cause membrane fouling. Therefore, when treating mine water, especially when selecting a membrane process, a membrane assembly with a negatively charged surface is preferred to effectively alleviate the problem of membrane fouling by utilizing the electrostatic repulsion effect.

[0006] In view of this, the present application is proposed. SUMMARY

[0007] The present application aims to provide a method for preparing a negatively charged polytetrafluoroethylene membrane, a negatively charged polytetrafluoroethylene membrane and its application. The negatively charged polytetrafluoroethylene membrane prepared by the method has excellent hydrophilicity and durability; at the same time, the electrostatic repulsion effect can be fully utilized to effectively alleviate the problem of membrane fouling.

[0008] In order to achieve the above-mentioned purpose of the present application, the following technical solutions are adopted: In a first aspect, the present application provides a method for preparing a negatively charged polytetrafluoroethylene membrane, which comprises the following steps: (1) placing a polytetrafluoroethylene membrane in an alcohol solution containing a siloxane coupling agent for the first soaking treatment; wherein the siloxane coupling agent is a bifunctional amino siloxane; (2) placing the polytetrafluoroethylene membrane treated in step (1) in an acidic aqueous solution for the second soaking treatment to complete the initial hydrolysis and dehydration condensation; (3) drying the polytetrafluoroethylene membrane treated in step (2) to complete the deep dehydration condensation; (4) first, the polytetrafluoroethylene film obtained by the treatment of step (3) and acyl halide are reacted, the atom transfer radical polymerization initiation site is bonded on the surface of the polytetrafluoroethylene film, then the atom transfer radical polymerization reaction of electron transfer activation and regeneration catalyst (electron transfer activation and regeneration catalyst atom transfer radical polymerization reaction, hereinafter referred to as ARGET ATRP) is carried out, the negatively charged hydrophilic monomer is grafted on the surface of the polytetrafluoroethylene film with initiation site, and the negatively charged polytetrafluoroethylene film is obtained.

[0009] Further, in step (1), the bifunctional amino siloxane is selected from bis[3-(trimethoxysilyl)propyl]amine and / or bis[3-(triethoxysilyl)propyl]amine.

[0010] Further, in step (1), the alcohol solution containing siloxane coupling agent includes, by mass percentage: siloxane coupling agent 0.2-12.5%, and the rest is an alcohol solvent.

[0011] Further, in step (1), the alcohol solvent is selected from ethanol and / or isopropanol.

[0012] Further, in step (1), the temperature of the first soaking treatment is 15-25°C.

[0013] Further, in step (1), the time of the first soaking treatment is 10-1440 min.

[0014] Further, in step (2), the pH of the acidic aqueous solution is 3.0-4.5.

[0015] Further, in step (2), the acidic aqueous solution includes an acidic solute and water.

[0016] Further, in step (2), the acidic solute is selected from any one or a combination of at least two of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.

[0017] Further, in step (2), the temperature of the second soaking treatment is 15-25°C.

[0018] Further, in step (2), the time of the second soaking treatment is 0.5-24 h.

[0019] Further, in step (3), the drying treatment is carried out in a drying oven.

[0020] Further, in step (3), the temperature of the drying treatment is 50-70°C.

[0021] Further, in step (3), the time of the drying treatment is 0.5-10 h.

[0022] Further, in step (4), the step of bonding the atom transfer radical polymerization initiation site specifically comprises: The polytetrafluoroethylene film obtained in step (3) is placed in a solution containing an acyl halide to perform a bonding reaction, thereby obtaining a polytetrafluoroethylene film with an initiation site.

[0023] Further, in step (4), the acyl halide is selected from 2-bromoisobutyryl bromide and / or 2-bromopropionyl bromide.

[0024] Further, in step (4), the solution containing an acyl halide comprises, by mass percentage: 0.1-5% of the acyl halide, and the balance being anhydrous medium.

[0025] Further, in step (4), the anhydrous medium comprises, by mass percentage: 0.1-5% of triethylamine, and the balance being tetrahydrofuran.

[0026] Further, in step (4), the bonding reaction is performed at a temperature of 0-25°C for a time period of 0.5-12 h.

[0027] Further, in step (4), the step of grafting the negatively charged hydrophilic monomer specifically comprises: The polytetrafluoroethylene film with an initiation site is placed in a solution containing a negatively charged hydrophilic monomer to perform a grafting reaction, thereby obtaining the negatively charged polytetrafluoroethylene film.

[0028] Further, in step (4), the solution containing a negatively charged hydrophilic monomer comprises, by concentration: 1-100 mM of the negatively charged hydrophilic monomer, 0.005-0.5 mM of a reducing agent, 0.01-1 mM of a catalyst, 0.03-3 mM of a ligand, and the balance being a solvent.

[0029] Further, in step (4), the negatively charged hydrophilic monomer is selected from sodium styrene sulfonate and / or acrylamido-2-methylpropane sulfonic acid.

[0030] Further, in step (4), the reducing agent is selected from any one or a combination of at least two of ascorbic acid, stannous iso-octoate, or silver powder.

[0031] Further, in step (4), the catalyst is selected from a divalent copper salt and / or a trivalent iron salt.

[0032] Further, in step (4), the ligand is selected from any one or a combination of at least two of N,N,N',N',N''-pentamethyldiethylenetriamine, iminodiacetic acid, tris-(3,6-dioxahexyl)amine, and triphenylphosphine.

[0033] Further, in step (4), in the solution containing a negatively charged hydrophilic monomer, the solvent is an aqueous ethanol solution.

[0034] Further, the temperature of the grafting reaction is 20-25℃, and the time of the grafting reaction is 0.5-6 h.

[0035] In a second aspect, the present application provides a negatively charged polytetrafluoroethylene membrane, which is prepared by the preparation method of the first aspect. Further, the initial contact angle of the negatively charged polytetrafluoroethylene membrane is 50-60°, and the Zeta potential of the negatively charged polytetrafluoroethylene membrane is -50--30 mV.

[0036] In a third aspect, the present application provides a use of the negatively charged polytetrafluoroethylene membrane of the first aspect in the preparation of a product for mine water treatment.

[0037] Compared with the prior art, the present application has the following beneficial effects: (1) In the preparation method of the negatively charged polytetrafluoroethylene membrane, a bifunctional amino siloxane is selected as a coupling agent, and then preliminary dehydration condensation and deep dehydration condensation treatment are performed to form a stable modified layer with high crosslinking degree, which provides a guarantee for long-term stability of hydrophilic performance; and the bifunctional amino siloxane also serves as a pre-modified active site, which provides a molecular interface for subsequent charge regulation of the surface of the polytetrafluoroethylene membrane.

[0038] (2) In the preparation method of the negatively charged polytetrafluoroethylene membrane, ARGET ATRP technology is used for surface charge modification of the polytetrafluoroethylene membrane, so as to precisely control the growth of the modified layer and avoid the risk of membrane hole blockage, and the stability of the negatively charged functional layer chemically bonded to the membrane surface is higher.

[0039] (3) The preparation method of the negatively charged polytetrafluoroethylene membrane is more simple and efficient, and the negatively charged polytetrafluoroethylene membrane prepared therefrom has excellent hydrophilicity and long-term charge effect, thereby effectively inhibiting the adsorption and accumulation of pollutants, and showing the dual advantages of service life and filtration efficiency. BRIEF DESCRIPTION OF DRAWINGS

[0040] In order to more clearly illustrate the specific embodiments of the present application or the technical solutions in the prior art, the drawings needed in the specific embodiments or the prior art description will be briefly introduced as follows. Obviously, the drawings in the following description are some embodiments of the present application, and other drawings can also be obtained by those skilled in the art without creative labor.

[0041] Figure 1 EDS diagram showing Si distribution of the negatively charged polytetrafluoroethylene membrane of Example 2.

[0042] Figure 2 SEM image of the outer wall of the negatively charged polytetrafluoroethylene membrane of Comparative Example 3. DETAILED DESCRIPTION

[0043] Unless otherwise defined, scientific and technical terms used in connection with the present application shall have the meanings that are commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear; however, in the event of any latent ambiguity, definitions provided herein take precedent over any dictionary or extrinsic definition. In this application, the use of "or" means "and / or" unless specifically stated otherwise, e.g., "comprising A or B" means "comprising A or B or both". Also, the use of "comprising" or other forms of "including", such as "including", "includes", "containing", "contains", or "having", are not intended to be limiting.

[0044] The technical solutions of the present application will be described clearly and completely below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.

[0045] In a first aspect, the present application provides a method for preparing a negatively charged polytetrafluoroethylene membrane, comprising the following steps: (1) placing a polytetrafluoroethylene membrane in an alcohol solution containing a siloxane coupling agent for first soaking treatment; wherein the siloxane coupling agent is a bifunctional amino siloxane; (2) placing the polytetrafluoroethylene membrane treated in step (1) in an acidic aqueous solution for second soaking treatment to complete initial hydrolysis and dehydration condensation; (3) drying the polytetrafluoroethylene membrane treated in step (2) to complete deep dehydration condensation; (4) first reacting the polytetrafluoroethylene membrane treated in step (3) with an acyl halide to bond atom transfer radical polymerization initiation sites on the surface of the polytetrafluoroethylene membrane, and then performing an electron transfer activation regeneration catalyst atom transfer radical polymerization reaction to graft negatively charged hydrophilic monomers on the surface of the polytetrafluoroethylene membrane with initiation sites, thereby obtaining the negatively charged polytetrafluoroethylene membrane.

[0046] In the present application, the method for preparing the negatively charged polytetrafluoroethylene membrane comprises sequentially performing PTFE membrane adsorption of small molecule modifier (bifunctional amino siloxane), PTFE membrane hydrolysis and initial dehydration condensation, PTFE membrane deep dehydration condensation, and PTFE membrane negatively charged modification.

[0047] Firstly, in step (1) of the present application, a bifunctional amino siloxane is selected as a coupling agent / small molecule modifier, which is hydrolyzed and condensed through the trialkoxysilane groups on both sides, so that a hydrophilic functional layer (a stable modified layer with high crosslinking degree) can be generated on the surface and in the pores of the PTFE membrane after the preliminary hydrolysis and dehydration condensation and deep dehydration condensation treatment in steps (2)-(3), thereby obtaining a PTFE membrane with persistent and stable hydrophilicity. This structure can firmly coat the surface of the PTFE fiber, providing a guarantee for the long-term stability of hydrophilicity, which is a significant advantage of the present application compared with the prior art. In addition, the secondary amine group in the silane coupling agent selected in the present application not only participates in hydrophilic modification, but also serves as a pre-modified active site, providing a molecular interface for subsequent charge regulation of the PTFE membrane surface.

[0048] Further, in step (4) of the present application, the PTFE membrane is first reacted with an acid halide in anhydrous medium for a certain period of time to bond an atom transfer radical polymerization (ATRP) initiation site to the surface of the PTFE membrane, and then a negatively charged hydrophilic monomer is grafted to the surface of the PTFE membrane using the ARGET ATRP technology of electron transfer catalyst generation, thereby obtaining a durable and negatively charged PTFE membrane. The advantage of using this ARGET ATRP technology for surface charge modification of the PTFE membrane is that this technology can precisely control the growth of the modified layer, thereby effectively avoiding the risk of pore blockage that often occurs in traditional methods, and the stability of the negatively charged functional layer chemically bonded to the membrane surface is higher. Therefore, the PTFE membrane prepared by the present application has excellent hydrophilicity and long-term charge effect. This is due to the simultaneous realization of stable hydrophilicity and charge characteristics on the surface and in the pores of the membrane, which can effectively inhibit the adsorption and accumulation of pollutants, thereby showing the dual advantages of service life and filtration efficiency.

[0049] As an optional embodiment, in step (1), the bifunctional amino siloxane is selected from bis[3-(trimethoxysilyl)propyl]amine and / or bis[3-(triethoxysilyl)propyl]amine.

[0050] As an optional embodiment, in step (1), the alcohol solution containing the siloxane coupling agent includes, by mass percentage: 0.2-12.5% of the siloxane coupling agent, and the balance being an alcohol solvent.

[0051] As an optional embodiment, the mass percentage of the siloxane coupling agent in the alcohol solution containing the siloxane coupling agent is 0.2-12.5%, for example, it can be 0.2%, 0.3%, 0.4%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 12.5%, etc., based on 100% of the mass of the alcohol solution containing the siloxane coupling agent.

[0052] As a preferred embodiment, the content of the siloxane coupling agent is 5 to 10% by mass, based on 100% of the mass of the alcohol solution of the siloxane coupling agent.

[0053] As an optional embodiment, in step (1), the alcohol solvent is selected from ethanol and / or isopropanol.

[0054] As an optional embodiment, in step (1), the temperature of the first immersion treatment is 15 to 25°C, for example, it can be 15°C, 16°C, 18°C, 20°C, 22°C, 24°C, 25°C, or the like.

[0055] As an optional embodiment, in step (1), the time of the first immersion treatment is 10 to 1440 min, for example, it can be 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 100 min, 120 min, 150 min, 200 min, 240 min, 300 min, 400 min, 500 min, 600 min, 700 min, 800 min, 900 min, 1000 min, 1100 min, 1200 min, 1300 min, 1400 min, 1440 min, or the like.

[0056] As a preferred embodiment, in step (1), the time of the first immersion treatment is 60 to 600 min.

[0057] As a preferred embodiment, in step (1), after the first immersion treatment, a step of taking out and drying is further included.

[0058] As a preferred embodiment, in step (1), the drying is room temperature air drying.

[0059] As an optional embodiment, in step (2), the pH of the acidic aqueous solution is 3.0 to 4.5, for example, it can be 3.0, 3.2, 3.4, 3.5, 3.6, 3.8, 4.0, 4.2, 4.4, 4.5, or the like.

[0060] As an optional embodiment, in step (2), the acidic aqueous solution includes an acidic solute and water.

[0061] As an optional embodiment, in step (2), the acidic solute is selected from any one or a combination of at least two of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.

[0062] As an optional embodiment, in step (2), the temperature of the second soaking treatment is 15-25℃, for example, it can be 15℃, 16℃, 18℃, 20℃, 22℃, 24℃, 25℃, etc.

[0063] As an optional embodiment, in step (2), the time of the second soaking treatment is 0.5-24 h, for example, it can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h, etc.

[0064] As a preferred embodiment, in step (2), the time of the second soaking treatment is 3-24 h.

[0065] As an optional embodiment, in step (2), after the second soaking treatment, a step of taking out is further included.

[0066] As an optional embodiment, in step (3), the drying treatment is carried out in a drying oven.

[0067] As an optional embodiment, in step (3), the temperature of the drying treatment is 50-70℃, for example, it can be 50℃, 52℃, 54℃, 56℃, 58℃, 60℃, 62℃, 64℃, 68℃, 70℃, etc.

[0068] As a preferred embodiment, in step (3), the temperature of the drying treatment is 60-70℃.

[0069] As an optional embodiment, in step (3), the time of the drying treatment is 0.5-10 h, for example, it can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, etc.

[0070] As a preferred embodiment, in step (3), the time of the drying treatment is 3-6 h.

[0071] As an optional embodiment, in step (4), the step of bonding atom transfer radical polymerization initiation site specifically includes: The polytetrafluoroethylene film obtained in step (3) is placed in a solution containing acyl halide to carry out a bonding reaction, and a polytetrafluoroethylene film with initiation site is obtained.

[0072] As an optional embodiment, in step (4), the acyl halide is selected from 2-bromoisobutyryl bromide and / or 2-bromopropionyl bromide.

[0073] As an optional embodiment, in step (4), the acyl halide-containing solution comprises, by mass percentage, acyl halide 0.1-5%, and the balance is anhydrous medium.

[0074] As an optional embodiment, the content of acyl halide in the acyl halide-containing solution is 0.1-5%, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or the like, based on 100% of the mass of the acyl halide-containing solution.

[0075] As an optional embodiment, in step (4), the anhydrous medium comprises, by mass percentage, triethylamine 0.1-5%, and the balance is tetrahydrofuran (THF).

[0076] As an optional embodiment, the content of triethylamine in the anhydrous medium is 0.1-5%, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or the like, based on 100% of the mass of the anhydrous medium.

[0077] As an optional embodiment, in step (4), the bonding reaction is performed at a temperature of 0-25°C, for example, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, and the bonding reaction is performed for a time of 0.5-12 h, for example, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, or the like.

[0078] As an optional embodiment, in step (4), the step of grafting the negatively charged hydrophilic monomer specifically comprises: placing the polytetrafluoroethylene film having an initiation site in a solution containing the negatively charged hydrophilic monomer to perform a grafting reaction, thereby obtaining the negatively charged polytetrafluoroethylene film.

[0079] As an optional embodiment, in step (4), the solution containing the negatively charged hydrophilic monomer comprises, by concentration, negatively charged hydrophilic monomer 1-100 mM, reducing agent 0.005-0.5 mM, catalyst 0.01-1 mM, ligand 0.03-3 mM, and the balance is solvent.

[0080] As an optional embodiment, the concentration of the negatively charged hydrophilic monomer in the solution containing the negatively charged hydrophilic monomer is 1-100 mM, for example, 1 mM, 10 mM, 15 mM, 20 mM, 25 mM, 30 mM, 35 mM, 40 mM, 45 mM, 50 mM, 55 mM, 60 mM, 65 mM, 70 mM, 75 mM, 80 mM, 85 mM, 90 mM, 95 mM, 100 mM, or the like.

[0081] As an optional embodiment, the concentration of the reducing agent in the solution containing the negatively charged hydrophilic monomer is 0.005-0.5 mM, for example, it can be 0.005 mM, 0.01 mM, 0.05 mM, 0.1 mM, 0.2 mM, 0.3 mM, 0.4 mM, 0.5 mM, etc.

[0082] As an optional embodiment, the concentration of the catalyst in the solution containing the negatively charged hydrophilic monomer is 0.01-1 mM, for example, it can be 0.01 mM, 0.05 mM, 0.1 mM, 0.2 mM, 0.3 mM, 0.4 mM, 0.5 mM, 0.6 mM, 0.7 mM, 0.8 mM, 0.9 mM, 1 mM, etc.

[0083] As an optional embodiment, the concentration of the ligand in the solution containing the negatively charged hydrophilic monomer is 0.03-3 mM, for example, it can be 0.03 mM, 0.05 mM, 0.1 mM, 0.2 mM, 0.4 mM, 0.6 mM, 0.8 mM, 1 mM, 1.5 mM, 2 mM, 2.5 mM, 3 mM, etc.

[0084] As an optional embodiment, in step (4), the negatively charged hydrophilic monomer is selected from sodium styrene sulfonate and / or acrylamido-2-methylpropane sulfonic acid.

[0085] As an optional embodiment, in step (4), the reducing agent is selected from any one or a combination of at least two of ascorbic acid, stannous iso-octoate, or silver powder.

[0086] As an optional embodiment, in step (4), the catalyst is selected from a divalent copper salt and / or a trivalent iron salt.

[0087] As an optional embodiment, in step (4), the ligand is selected from any one or a combination of at least two of N,N,N',N',N''-pentamethyldiethylenetriamine (PMDETA), iminodiacetic acid (IDA), tris-(3,6-dioxaheptyl)amine (TDA-1), and triphenylphosphine (PPh3).

[0088] As an optional embodiment, in step (4), in the solution containing the negatively charged hydrophilic monomer, the solvent is an aqueous ethanol solution.

[0089] As an optional embodiment, the temperature of the grafting reaction is 20-25℃, for example, it can be 20℃, 21℃, 22℃, 23℃, 24℃, 25℃, etc., and the time of the grafting reaction is 0.5-6 h, for example, it can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, etc.

[0090] In a second aspect, the present application provides a negatively charged polytetrafluoroethylene membrane, which is prepared by the preparation method of the first aspect.

[0091] In the present application, the prepared negatively charged polytetrafluoroethylene membrane is a hydrophilic and durable negatively charged polytetrafluoroethylene (PTFE) membrane, specifically a hydrophilic and durable negatively charged PTFE membrane that can be applied to mine water treatment.

[0092] As an optional embodiment, the initial contact angle of the negatively charged polytetrafluoroethylene membrane is 50-60°, for example, it can be 50°, 51°, 52°, 53°, 54°, 55°, 56°, 57°, 58°, 59°, 60°, etc.

[0093] As an optional embodiment, the Zeta potential of the negatively charged polytetrafluoroethylene membrane is -50--30 mV, for example, it can be -50 mV, -48 mV, -46 mV, -44 mV, -42 mV, -40 mV, -38 mV, -36 mV, -34 mV, -32 mV, -30 mV, etc.

[0094] As an optional embodiment, the negatively charged polytetrafluoroethylene membrane can withstand acid (HCl solution with pH = 2), alkali (NaOH solution with pH = 12), and oxidizing agent (1000 ppm NaClO solution) cleaning.

[0095] In a third aspect, the present application provides a use of the negatively charged polytetrafluoroethylene membrane of the first aspect in the preparation of a product for mine water treatment.

[0096] The present application will be further described by examples. Unless otherwise specified, the materials in the examples are prepared according to the existing methods or directly purchased from the market.

[0097] Example 1 The present example provides a preparation method of a hydrophilic and durable negatively charged PTFE membrane, which specifically comprises the following steps: (1) The PTFE membrane is placed in a 5 w.t.% solution of bis[3-(trimethoxysilyl)propyl]amine in ethanol, soaked at 15℃ for 600 min, and then taken out and dried at room temperature; (2) The PTFE membrane treated in step (1) is immersed in an aqueous solution of hydrochloric acid with pH 3.0 at 25°C for 3 h to complete the initial hydrolysis and dehydration condensation, and then taken out; (3) The PTFE membrane treated in step (2) is placed in a drying oven at 60°C for 6 h to perform deep dehydration condensation, and a hydrophilic functional layer is formed on the surface and in the pores of the membrane, and then taken out; (4) The PTFE membrane treated in step (3) is placed in a THF solution containing 1 w.t.% of 2-bromoisobutyryl bromide and 2 w.t.% of triethylamine at 0°C for 1.5 h, and then taken out and dried at room temperature. Then, the PTFE membrane is placed in a conical flask, 100 mL of an aqueous solution containing 20 vol% of ethanol, 5 mmol of sodium styrene sulfonate, 0.001 mmol of CuBr2 and 0.01 mmol of PMDETA are sequentially added, argon is bubbled in the system for 10 min to remove most of the air, then 0.005 mmol of ascorbic acid is added, the flask is sealed, and the reaction is performed at room temperature for 2 h. After the reaction is completed, the membrane is washed with pure water and dried at room temperature.

[0098] Example 2 The present embodiment provides a preparation method of a hydrophilic durable negatively charged PTFE membrane, which specifically comprises the following steps: (1) The PTFE membrane is immersed in an ethanol solution of 10 w.t.% of bis[3-(trimethoxysilyl)propyl]amine at 25°C for 60 min, and then taken out and dried at room temperature; (2) The PTFE membrane treated in step (1) is immersed in an aqueous solution of nitric acid with pH 3.0 at 15°C for 3 h to complete the initial hydrolysis and dehydration condensation, and then taken out; (3) The PTFE membrane treated in step (2) is placed in a drying oven at 60°C for 6 h to perform deep dehydration condensation, and a hydrophilic functional layer is formed on the surface and in the pores of the membrane, and then taken out; (4) The PTFE membrane treated in step (3) is placed in a THF solution containing 1 w.t.% of 2-bromoisobutyryl bromide and 2 w.t.% of triethylamine at 5°C for 1.5 h, and then taken out and dried at room temperature. Then, the PTFE membrane is placed in a conical flask, 100 mL of an aqueous solution containing 20 vol% of ethanol, 5 mmol of sodium styrene sulfonate, 0.001 mmol of CuBr2 and 0.01 mmol of PMDETA are sequentially added, argon is bubbled in the system for 10 min to remove most of the air, then 0.005 mmol of ascorbic acid is added, the flask is sealed, and the reaction is performed at room temperature for 2 h. After the reaction is completed, the membrane is washed with pure water and dried at room temperature.

[0099] Figure 1EDS mapping showing Si distribution across the section of the hydrophilic and durable negatively charged PTFE membrane of Example 2. As shown, Si is uniformly distributed across the cross-section of the PTFE hollow fiber membrane. Figure 1

[0100] Example 3 The present example provides a method for preparing a hydrophilic and durable negatively charged PTFE membrane, which specifically comprises the following steps: (1) PTFE membrane is placed in a 5 w.t.% solution of bis[3- (triethoxysilyl) propyl] amine in ethanol and isopropanol (v / v = 1 / 1), and soaked at 25°C for 60 min, then taken out and air-dried at room temperature; (2) The PTFE membrane treated in step (1) is placed in a pH 3.0 aqueous solution of phosphoric acid, and soaked at 25°C for 3 h to complete the initial hydrolysis and dehydration condensation, and then taken out; (3) The PTFE membrane treated in step (2) is placed in a drying oven at 60°C for 6 h to perform deep dehydration condensation, and a hydrophilic functional layer is formed on the membrane surface and in the membrane pores, and then taken out; (4) The PTFE membrane treated in step (3) is placed in a THF solution containing 1 w.t.% 2-bromoisobutyryl bromide and 2 w.t.% triethylamine, and reacted at 15°C for 6 h, and then taken out and air-dried at room temperature; then, the PTFE membrane is placed in a conical flask, and 100 mL of an aqueous solution containing 20 vol% ethanol, 5 mmol of sodium styrene sulfonate, 0.001 mmol of CuBr2, and 0.01 mmol of PMDETA are sequentially added, the system is purged with argon for 10 min to remove most of the air, then 0.005 mmol of ascorbic acid is added, the flask is sealed, and the reaction is performed at room temperature for 2 h; after the reaction is completed, the membrane is washed with pure water and air-dried at room temperature.

[0101] Example 4 The present example provides a method for preparing a hydrophilic and durable negatively charged PTFE membrane, which specifically comprises the following steps: (1) PTFE membrane is placed in a 10 w.t.% solution of bis[3- (trimethoxysilyl) propyl] amine in ethanol, and soaked at 25°C for 60 min, then taken out and air-dried at room temperature; (2) The PTFE membrane treated in step (1) is placed in a pH 4.5 aqueous solution of sulfuric acid, and soaked at 25°C for 24 h to complete the initial hydrolysis and dehydration condensation, and then taken out; (3) The PTFE membrane treated in step (2) is placed in a drying oven at 60°C for 6 h to perform deep dehydration condensation, and a hydrophilic functional layer is formed on the membrane surface and in the membrane pores, and then taken out; ​(4) The PTFE membrane obtained in step (3) is placed in a THF solution containing 1 w.t.% 2-bromoisobutyryl bromide and 2 w.t.% triethylamine, and reacted at 25°C for 1 h. The membrane is taken out and dried at room temperature. Then, the PTFE membrane is placed in a conical flask, and 100 mL of an aqueous solution containing 20 vol% ethanol, 5 mmol of sodium styrene sulfonate, 0.001 mmol of CuBr2, and 0.01 mmol of PMDETA are sequentially added. The system is purged with argon for 10 min to remove most of the air, and then 0.005 mmol of ascorbic acid is added. The flask is sealed and reacted at room temperature for 2 h. After the reaction is completed, the membrane is washed with pure water and dried at room temperature.

[0102] Example 5 The present embodiment provides a method for preparing a hydrophilic and durable negatively charged PTFE membrane, which specifically comprises the following steps: (1) The PTFE membrane is placed in a 10 w.t.% ethanol solution of bis[3- (trimethoxysilyl) propyl] amine, and soaked at 25°C for 60 min. The membrane is taken out and dried at room temperature. (2) The PTFE membrane obtained in step (1) is placed in a pH 3.0 aqueous hydrochloric acid solution, and soaked at 25°C for 3 h to complete the initial hydrolysis, dehydration and condensation. The membrane is taken out. (3) The PTFE membrane obtained in step (2) is placed in a 70°C drying oven for 3 h to perform deep dehydration and condensation, and generate a hydrophilic functional layer on the surface and inside the pores of the membrane. The membrane is taken out. (4) The PTFE membrane obtained in step (3) is placed in a THF solution containing 1 w.t.% 2-bromoisobutyryl bromide and 2 w.t.% triethylamine, and reacted at 5°C for 1.5 h. The membrane is taken out and dried at room temperature. Then, the PTFE membrane is placed in a conical flask, and 100 mL of an aqueous solution containing 20 vol% ethanol, 5 mmol of sodium styrene sulfonate, 0.001 mmol of CuBr2, and 0.01 mmol of PMDETA are sequentially added. The system is purged with argon for 10 min to remove most of the air, and then 0.005 mmol of ascorbic acid is added. The flask is sealed and reacted at room temperature for 2 h. After the reaction is completed, the membrane is washed with pure water and dried at room temperature.

[0103] Example 6 The present embodiment provides a method for preparing a hydrophilic and durable negatively charged PTFE membrane, which specifically comprises the following steps: (1) The PTFE membrane is placed in a 10 w.t.% ethanol solution of bis[3- (trimethoxysilyl) propyl] amine, and soaked at 25°C for 60 min. The membrane is taken out and dried at room temperature. (2) The PTFE membrane treated in step (1) is immersed in a water solution of sulfuric acid with pH 3.0 at 25°C for 3 h to complete the initial hydrolysis and dehydration condensation, and then taken out; (3) The PTFE membrane treated in step (2) is placed in a drying oven at 70°C for 3 h to perform deep dehydration condensation, and a hydrophilic functional layer is formed on the surface and in the pores of the membrane, and then taken out; (4) The PTFE membrane treated in step (3) is placed in a THF solution containing 5.0 w.t.% 2-bromoisobutyryl bromide and 2 w.t.% triethylamine at 25°C for 0.3 h, and then taken out and dried at room temperature. Then, the PTFE membrane is placed in a conical flask, 100 mL of a water solution containing 20 vol% ethanol, 5 mmol of sodium styrene sulfonate, 0.001 mmol of CuBr2 and 0.01 mmol of PMDETA are sequentially added, the system is purged with argon for 10 min to remove most of the air, then 0.005 mmol of ascorbic acid is added, the flask is sealed, and the reaction is performed at room temperature for 2 h. After the reaction is completed, the membrane is washed with pure water and dried at room temperature.

[0104] Example 7 The embodiment provides a preparation method of a hydrophilic durable negatively charged PTFE membrane, and specifically comprises the following steps: (1) The PTFE membrane is immersed in a 10 w.t.% ethanol solution of bis[3-(trimethoxysilyl)propyl]amine at 25°C for 60 min, and then taken out and dried at room temperature; (2) The PTFE membrane treated in step (1) is immersed in a water solution of sulfuric acid with pH 3.0 at 25°C for 3 h to complete the initial hydrolysis and dehydration condensation, and then taken out; (3) The PTFE membrane treated in step (2) is placed in a drying oven at 70°C for 3 h to perform deep dehydration condensation, and a hydrophilic functional layer is formed on the surface and in the pores of the membrane, and then taken out; (4) The PTFE membrane treated in step (3) is placed in a THF solution containing 1 w.t.% 2-bromoisobutyryl bromide and 2 w.t.% triethylamine at 5°C for 1.5 h, and then taken out and dried at room temperature. Then, the PTFE membrane is placed in a conical flask, 100 mL of a water solution containing 20 vol% ethanol, 5 mmol of acrylamido-2-methylpropane sulfonic acid, 0.05 mmol of FeCl3·6H2O and 0.5 mmol of PPh3 are sequentially added, the system is purged with argon for 10 min to remove most of the air, then 0.25 mmol of stannous iso-octoate is added, the flask is sealed, and the reaction is performed at room temperature for 2 h. After the reaction is completed, the membrane is washed with pure water and dried at room temperature.

[0105] Example 8 The present embodiment provides a method for preparing a hydrophilic and durable negatively charged PTFE membrane, which specifically comprises the following steps: (1) PTFE membrane is placed in a 10 w.t.% solution of bis[3-(trimethoxysilyl)propyl]amine in ethanol, and soaked at 25°C for 60 min, then taken out and dried at room temperature; (2) The PTFE membrane treated in step (1) is placed in a pH 3.0 aqueous solution of sulfuric acid, and soaked at 25°C for 3 h to complete the initial hydrolysis and dehydration condensation, and then taken out; (3) The PTFE membrane treated in step (2) is placed in a drying oven at 70°C for 3 h to perform deep dehydration condensation, and a hydrophilic functional layer is formed on the surface and in the pores of the membrane, and then taken out; (4) The PTFE membrane treated in step (3) is placed in a THF solution containing 1 w.t.% 2-bromoisobutyryl bromide and 2 w.t.% triethylamine, and reacted at 10°C for 1.5 h, and then taken out and dried at room temperature; then, the PTFE membrane is placed in a conical flask, 100 mL of an aqueous solution containing 20 vol% ethanol, 10 mmol of sodium styrene sulfonate, 0.002 mmol of CuBr2, and 0.01 mmol of PMDETA are sequentially added, the system is purged with argon for 10 min to remove most of the air, then 0.01 mmol of ascorbic acid is added, sealed, and reacted at room temperature for 1 h; after the reaction is completed, the membrane is washed with pure water and dried at room temperature.

[0106] Comparative Example 1 The present comparative example provides an original PTFE membrane without modification.

[0107] Comparative Example 2 The present comparative example provides a method for preparing a hydrophilic PTFE membrane, which specifically comprises the following steps: (1) PTFE membrane is placed in a 10 w.t.% solution of bis[3-(trimethoxysilyl)propyl]amine in ethanol, and soaked at 25°C for 60 min, then taken out and dried at room temperature; (2) The PTFE membrane treated in step (1) is placed in a pH 3.0 aqueous solution of sulfuric acid, and soaked at 25°C for 3 h to complete the initial hydrolysis and dehydration condensation, and then taken out.

[0108] Comparative Example 3 The present comparative example provides a method for preparing a hydrophilic PTFE membrane, which specifically comprises the following steps: (1) PTFE membrane is placed in a 10 w.t.% solution of bis[3-(trimethoxysilyl)propyl]amine in ethanol, and soaked at 25°C for 60 min, then taken out and dried at room temperature; (2) The PTFE membrane treated in step (1) is immersed in a water solution of sulfuric acid with pH 3.0 at 25°C for 3 h, to complete the initial hydrolysis and dehydration condensation, and then taken out; (3) The PTFE membrane treated in step (2) is placed in a drying oven at 60°C for 6 h, to perform deep dehydration condensation, and generate a hydrophilic functional layer on the surface of the membrane and in the membrane holes, and then taken out.

[0109] Figure 2 The SEM image of the outer wall of the hydrophilic and durable negatively charged PTFE membrane of Comparative Example 3 is shown. As shown in the SEM image, the pore structure of the outer surface of the PTFE membrane still exists, and the modification process does not cause the membrane holes to be blocked. Figure 2

[0110] Comparative Example 4 This comparative example provides a method for preparing a hydrophilic PTFE membrane, which is different from Example 1 in that the bis[3-(trimethoxysilyl)propyl]amine in step (1) is replaced with an equal amount of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane (KH792), and the other steps are consistent with Example 1.

[0111] Comparative Example 5 This comparative example provides a method for preparing a hydrophilic PTFE membrane, which is different from Example 1 in that the bis[3-(trimethoxysilyl)propyl]amine in step (1) is replaced with an equal amount of vinyltriethoxysilane, and the other steps are consistent with Example 1.

[0112] Comparative Example 6 This comparative example provides a method for preparing a hydrophilic PTFE membrane, which is different from Example 1 in that the bis[3-(trimethoxysilyl)propyl]amine in step (1) is replaced with an equal amount of gamma glycidyl ether propyltrimethoxysilane, and the other steps are consistent with Example 1.

[0113] Test Example 1 Test samples: hydrophilic and durable negatively charged PTFE membranes provided by Examples 1-8, unmodified original PTFE membrane provided by Comparative Example 1, and hydrophilic PTFE membranes provided by Comparative Examples 2-6.

[0114] Test method: The hydrophilic, durable, and charged PTFE membranes prepared are tested for hydrophilicity, durability, and charge. The PTFE membrane filaments are placed in an oven at 40°C for 24 h, and then subjected to characterization tests, as shown below: (1) Hydrophilicity test: static contact angle test is used.

[0115] ​(2) Durability resistance test: the PTFE membrane was immersed in HCl solution with pH = 2, NaOH solution with pH = 12 and NaClO solution with 1000 ppm for 10 days respectively, and after washing the acid, alkali or oxidant with pure water and drying completely, the contact angle test was carried out to investigate the hydrophilicity of the PTFE membrane.

[0116] (3) Chargeability potential test: Zeta potential instrument was used to test the potential value at pH 7.0.

[0117] The specific test results are shown in Table 1: Table 1

[0118] The data in Table 1 above show that after modification by ARGET ATRP technology, the surface properties of the PTFE membrane have been fundamentally changed: the water contact angle is significantly reduced from ~133° of the original membrane to below 60°, and the Zeta potential is shifted from ~-15 mV to ~-35.6~-49.2 mV, which indicates that the hydrophilicity and negative charge of the membrane surface have been simultaneously achieved and precisely controlled. More importantly, the examples show that after 10 days of accelerated aging of the modified membrane in acid, alkali and oxidant, the above-mentioned key performance parameters remain stable. This result fully proves that the functional layer constructed by the method of the present application is extremely firmly combined with the PTFE fiber substrate, and can withstand the harsh chemical cleaning conditions in actual use, ensuring the durability of the performance.

[0119] Finally, it should be noted that: the above examples are only used to illustrate the technical solutions of the present application, but not to limit them; although the present application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that: it can still modify the technical solutions recorded in the foregoing examples, or make equivalent replacement for part or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a negatively charged polytetrafluoroethylene membrane, characterized in that, The method for preparing the negatively charged polytetrafluoroethylene membrane includes the following steps: (1) The polytetrafluoroethylene membrane is placed in an alcohol solution containing a siloxane coupling agent for a first immersion treatment; wherein the siloxane coupling agent is a bifunctional aminosiloxane. (2) The polytetrafluoroethylene membrane obtained in step (1) is placed in an acidic aqueous solution for a second immersion treatment to complete the preliminary hydrolysis and dehydration condensation. (3) The polytetrafluoroethylene membrane obtained in step (2) is dried to complete the deep dehydration condensation. (4) First, react the polytetrafluoroethylene membrane obtained in step (3) with the acyl halide. After bonding the atom transfer radical polymerization initiation site to the surface of the polytetrafluoroethylene membrane, the electron transfer activation and regeneration catalyst atom transfer radical polymerization reaction is carried out. The negatively charged hydrophilic monomer is grafted onto the surface of the polytetrafluoroethylene membrane with the initiation site to obtain the negatively charged polytetrafluoroethylene membrane.

2. The method for preparing a negatively charged polytetrafluoroethylene membrane according to claim 1, characterized in that, In step (1), the bifunctional aminosiloxane is selected from bis[3-(trimethoxysilyl)propyl]amine and / or bis[3-(triethoxysilyl)propyl]amine; In step (1), the alcohol solution containing siloxane coupling agent comprises, by mass percentage: 0.2-12.5% ​​siloxane coupling agent, with the remainder being alcohol solvent; In step (1), the alcohol solvent is selected from ethanol and / or isopropanol.

3. The method for preparing a negatively charged polytetrafluoroethylene membrane according to claim 1, characterized in that, In step (1), the temperature of the first soaking treatment is 15~25℃; And / or, in step (1), the first soaking treatment time is 10~1440 min.

4. The method for preparing a negatively charged polytetrafluoroethylene membrane according to claim 1, characterized in that, In step (2), the pH of the acidic aqueous solution is 3.0~4.5; And / or, in step (2), the acidic aqueous solution comprises an acidic solute and water; In step (2), the acidic solute is selected from any one or at least a combination of two of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.

5. The method for preparing a negatively charged polytetrafluoroethylene membrane according to claim 1, characterized in that, In step (2), the temperature of the second soaking treatment is 15~25℃; And / or, in step (2), the second soaking treatment time is 0.5~24 h.

6. The method for preparing a negatively charged polytetrafluoroethylene membrane according to claim 1, characterized in that, In step (3), the drying process is carried out in a drying oven; And / or, in step (3), the drying temperature is 50~70℃; And / or, in step (3), the drying process takes 0.5 to 10 hours.

7. The method for preparing a negatively charged polytetrafluoroethylene membrane according to claim 1, characterized in that, In step (4), the step of transferring the bonded atom to the radical polymerization initiation site specifically includes: The polytetrafluoroethylene membrane obtained in step (3) is placed in a solution containing acyl halide to carry out a bonding reaction, thereby obtaining a polytetrafluoroethylene membrane with initiation sites. The acyl halide is selected from 2-bromoisobutyryl bromide and / or 2-bromopropionyl bromide; The acyl halide-containing solution comprises, by mass percentage: 0.1-5% acyl halide, with the remainder being anhydrous medium; The anhydrous medium comprises, by mass percentage: 0.1-5% triethylamine, with the balance being tetrahydrofuran; The bonding reaction is carried out at a temperature of 0~25℃ for 0.5~12 h.

8. The method for preparing a negatively charged polytetrafluoroethylene membrane according to claim 1, characterized in that, In step (4), the specific steps of grafting negatively charged hydrophilic monomers include: A polytetrafluoroethylene membrane with initiation sites is placed in a solution containing a negatively charged hydrophilic monomer and a grafting reaction is carried out to obtain the negatively charged polytetrafluoroethylene membrane. The solution containing the negatively charged hydrophilic monomer comprises, by concentration: 1-100 mM of the negatively charged hydrophilic monomer, 0.005-0.5 mM of the reducing agent, 0.01-1 mM of the catalyst, 0.03-3 mM of the ligand, and the remainder is solvent; The negatively charged hydrophilic monomer is selected from sodium styrene sulfonate and / or acrylamido-2-methylpropanesulfonic acid; The reducing agent is selected from any one or a combination of at least two of ascorbic acid, stannous isooctanoate, or silver powder; The catalyst is selected from divalent copper salts and / or trivalent iron salts; The ligand is selected from any one or a combination of at least two of N,N,N',N',N''-pentamethyldiethylenetriamine, iminodiacetic acid, tris-(3,6-dioxohepyl)amine, and triphenylphosphine; The solvent is an aqueous ethanol solution; The grafting reaction is carried out at a temperature of 20-25°C for 0.5-6 hours.

9. A negatively charged polytetrafluoroethylene membrane, characterized in that, The negatively charged polytetrafluoroethylene membrane is prepared by the preparation method according to any one of claims 1 to 8; The initial contact angle of the negatively charged polytetrafluoroethylene film is 50~60°, and the Zeta potential of the negatively charged polytetrafluoroethylene film is -50~-30 mV.

10. The use of a negatively charged polytetrafluoroethylene membrane according to claim 9 in the preparation of products for mine water treatment.

Citation Information

Patent Citations

  • Negative charge modified nanofiltration membrane and production process thereof

    CN115138211A

  • Hydrophilic polytetrafluoroethylene microporous membrane as well as preparation method and application thereof

    CN117959943A

  • Polymer brush for improving biomedical material compatibility and its preparing method

    CN1775313A

  • Porous film having hydrophilic graft polymer, method for using the same and method for producing the same

    JP2008248181A

  • Hydrophilic porous membrane manufacturing method

    JP2019130481A